Factores relacionados con la trasmisión del klepsiella pneumoniae en los pacientes de la unidad de cuidados intensivos - Armijos Hernández, Paola Fernanda (2025)
Background. Infections associated with health services (IAHS) are a global health issue. One of the most significant detected in ICU services is caused by the enterobacterium Klebsiella pneumoniae, an opportunistic pathogen that causes a wide spectrum of diseases, leading to public health concerns. Objective: Identify the factors related to the transmission of Klebsiella pneumonia in Intensive Care Unit patients. Methods: This qualitative study was supported by a review of scientific articles published in indexed journals. According to its structure is a descriptive study, it included various investigations such as postgraduate theses and international and national reports, excluding less relevant texts like newspapers or interviews. Results: The main risk factors were generally associated with prolonged mechanical ventilation, the use of enteral feeding tubes, central venous catheters, and inadequate hand hygiene. Conclusions: Preventive measures, hand hygiene controls, the use of biosecurity equipment, disinfection, sterilization, and active surveillance are crucial to preventing the spread of this pathogen. Continuous education for health personnel is paramount as the cornerstone.